2020
DOI: 10.1038/s41598-020-67979-3
|View full text |Cite
|
Sign up to set email alerts
|

Do pit-building predators prefer or avoid barriers? Wormlions' preference for walls depends on light conditions

Abstract: Ambush site selection by sit-and-wait predators is a complex process, involving biotic and abiotic considerations, which greatly affect hunting success and costs. Wormlions are fly larvae that dig pit-traps in loose soil and hunt the arthropod prey falling into their pits. They are abundant in urban environments, found below buildings that provide cover, and many of their pits are dug adjacent to walls. We examined here under what conditions wormlions prefer to dig their pits next to walls. We analysed our dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 75 publications
(49 reference statements)
1
7
0
Order By: Relevance
“…Regarding the pit area, the final location in deep or shallow sand had a stronger effect than the treatment per se, while the shade/light treatments were more important for the pit area than the final location. This fits previous studies indicating that while both deep sand and shade are preferred, sand depth affects the pit area more strongly 80 . The reason is probably that while deep sand is preferred in order to construct larger pits, shade is preferred in order to avoid exposure to high temperatures and desiccation 58 , 60 .…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the pit area, the final location in deep or shallow sand had a stronger effect than the treatment per se, while the shade/light treatments were more important for the pit area than the final location. This fits previous studies indicating that while both deep sand and shade are preferred, sand depth affects the pit area more strongly 80 . The reason is probably that while deep sand is preferred in order to construct larger pits, shade is preferred in order to avoid exposure to high temperatures and desiccation 58 , 60 .…”
Section: Discussionsupporting
confidence: 92%
“…Shade could present a better explanation for the wormlion apparent preference for walls. First, a series of lab experiments has demonstrated that wormlions prefer walls when these provide shade [45]. Second, wall positions were more shaded, at least temporarily, than positions more distant from walls at four of the seven sites examined.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study has suggested that wormlions prefer to dig pits next to walls or other barriers, but no quantitative support was provided for this suggestion regarding the wormlion's natural habitat [45]. In a series of lab experiments, wormlions chose to dig pits next to walls if these provided some shelter from direct light [45]. There are four possible reasons why pit positions next to walls should be preferred: (a) walls may provide shade for at least part of the day; (b) loose soil may accumulate next to walls driven by the wind and function as a "sand fence" [46,47], resulting in deeper soil in which to dig; (c) because wind carries fine particles more easily than coarse ones [48], sand next to walls may be finer than in other locations.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…It could also be that wind is not perceived as a ‘crucial’ problem, preventing hunting only temporally. In comparison, direct light, which correlates with high temperature leading to desiccation, as well as shallow sand, inhibiting pit construction, both trigger more relocation (Scharf et al., 2020). Relocation should also depend on the risk associated with movement, such as predation or cannibalism, and the pit construction costs.…”
Section: Discussionmentioning
confidence: 99%